2021
DOI: 10.3389/fcell.2021.796274
|View full text |Cite
|
Sign up to set email alerts
|

BBS7–SHH Signaling Activity Regulates Primary Cilia for Periodontal Homeostasis

Abstract: Objectives: Mechanical stimuli are essential for the maintenance of periodontal ligament (PDL) homeostasis. Although there are several studies on atrophic changes in PDL due to occlusal hypofunction, the underlying mechanism is still unknown. Here, we aimed to explore the changes of gene expression in occlusal hypofunctional PDL and elucidate the related role in maintaining the PDL homeostasis.Methods: To investigate the transcriptomic difference between control and hypofunctional PDL tissue from patients, RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…For PD, BBS7 is essential for periodontal ligament homeostasis through regulating primary cilia. BBS7 was downregulated in occlusal hypofunctional periodontal ligament, and knockdown of BBS7 could inhibit cell migration and angiogenesis ( Chang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For PD, BBS7 is essential for periodontal ligament homeostasis through regulating primary cilia. BBS7 was downregulated in occlusal hypofunctional periodontal ligament, and knockdown of BBS7 could inhibit cell migration and angiogenesis ( Chang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hematoxylin and eosin (HE) staining was performed after deparaffinization. For immunological staining of histological sections or cells, the following antibodies were used, as previously described [ 46 ]. Rabbit anti-CACNA1C (1:200, Alomone Labs, ACC-003), mouse anti-CK14 (1:500, Abcam, ab7800), mouse anti-CK10 (1:500, Invitrogen, MA5-13705), mouse anti-E-cadherin (1:500, BD Biosciences, AF748), rabbit anti-MMP-9 (1:200, Merck, AB19016), rabbit anti-LGR5 (1:200, Abcam, ab75732), mouse anti-Ki67 (1:200, Abcam, ab16667), mouse anti-PCNA (1:500, Abcam, ab29), mouse anti-NFATc1 (1:200, Santa Cruz, SC-7294), and mouse anti-β-catenin (1:500, Santa Cruz, SC-7963).…”
Section: Methodsmentioning
confidence: 99%
“…In fetal enamel organs, the primary cilium is expressed in enamel knots, which are signaling centers that signal mesenchymal tissues [ 117 ]. In other tooth-related tissues, the hypofunctional periodontal ligament (PDL) downregulates the expression of BBS7 by delaying cell migration and suppressing cell angiogenesis [ 141 ]. Recent studies have shown that the primary cilium has a close relationship not only with Hh, but also with WNT [ 142 ], fibroblast growth factor (FGF) [ 143 ], and PDGF [ 144 ].…”
Section: Hedgehog Signaling and Ciliopathymentioning
confidence: 99%